Electrochemical evaluation of water hyacinth–based activated carbon for energy storage devices using various KOH concentrations - Ríos-González, Juan A.; Martínez-Martínez, Vander; Padilla-Martínez, Erick D.; Sánchez-Rodríguez, César E.; López-Sandoval, Román (Next materials, 2025)
Activated carbon (ACs) with good electrochemical properties was obtained from water hyacinth. The biomass precursor was precarbonized using oxidative calcination at 300 °C in room conditions. Two approaches were used for impregnation of the porogenic agent at different molarities (1 M, 2 M, and 6 M KOH): (a) using magnetic stirring at room conditions and (b) with a reflux system at 100 °C. We found that temperature and molarity are key parameters for obtaining high specific surface areas and, hence, high specific capacitances (Cg) of the ACs. Those impregnated using reflux with KOH molarities 2 M and 6 M showed the best Cg (Cg= 216 and Cg= 215 F g−1 at 5 mV s−1, respectively), which is related to their high specific surface area (1620 and 1484 m2 g−1, respectively). In contrast, those impregnated with magnetic stirring at room conditions showed lower capacitances (Cg= 145.3 F g−1, 2 M KOH; Cg = 94.3 F g−1 6 M KOH, at 5 mV s−1). Both refluxed ACs were used for the fabrication of symmetric supercapacitors (SCs), which exhibited a power density of 14.3 kW kg−1 and an energy density of 4.5 W h kg−1 (2 M KOH), power density of 15 kW kg−1 and energy density of 4.7 W h kg−1 (6 M KOH). Although both ACs exhibit similar electrochemical properties, we consider that the one impregnated at low molarity with reflux is attractive from the economical and ecological point of view for use in SCs. [Display omitted] •Water hyacinth-derived AC shows high specific surface area.•Reflux impregnation improves KOH activation efficiency.•Optimized AC yields ∼216 F g⁻¹ capacitance.•AC morphology optimized via controlled pore size distribution.•Eco-friendly AC process tackles invasive water hyacinth.